Application of 24 factoral design in chitinase production from trichoderma virens - 494886 Zuraidah Mohamad; Arifah Bahar; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2007